The Moxon Tennyson a landmark in Victorian illustration - Cooke, Simon (Simon Gareth) (Series in Victorian studies, 2021)
Cooke's analysis of this milestone Victorian publication reveals the fluctuating harmony and dissonance between Tennyson's poems and their illustrations, the technical challenges and occupations involved in its manufacture, its readers' contemporary reception, and its subsequent influence as a variously revered and reviled publication.